2018
DOI: 10.14419/ijet.v7i4.35.22904
|View full text |Cite
|
Sign up to set email alerts
|

S55c Carbon Steel for Heat Treatment Process with Different Medium in Attenuation Measurement using Ultrasonic Testing

Abstract: Ultrasonic testing or commonly known as UT is one of the non-destructive testing technique and widely used in oil and gas industrial inspection. This technique mostly used in defect or crack identification of the pipeline and also used for flaw detection/evaluation, dimensional measurements, and material characterization. This paper presents the effect of heat treatment for S55C carbon steel in attenuation measurement by using ultrasonic testing including annealing, tempering, and quenching process.  Seawater … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Excitation setup, sensor alignment and locations, and the influence of various excitation and sensor setup characteristics, as well as the device under test, were all evaluated via finite element analysis. In light of these findings, a laboratory apparatus was constructed to investigate the impact of key measurement factors [38][39][40] [41]. Summaries of encircling coil system and Giant Magnetoresistance (GMR) sensor system According on Table 1 show the previous design and method used in Eddy Current Testing (ECT) inspection.…”
Section: Design On Combination With Giant Magneto Resistive Sensors A...mentioning
confidence: 99%
See 1 more Smart Citation
“…Excitation setup, sensor alignment and locations, and the influence of various excitation and sensor setup characteristics, as well as the device under test, were all evaluated via finite element analysis. In light of these findings, a laboratory apparatus was constructed to investigate the impact of key measurement factors [38][39][40] [41]. Summaries of encircling coil system and Giant Magnetoresistance (GMR) sensor system According on Table 1 show the previous design and method used in Eddy Current Testing (ECT) inspection.…”
Section: Design On Combination With Giant Magneto Resistive Sensors A...mentioning
confidence: 99%
“…Excitation setup, sensor alignment and locations, and the influence of various excitation and sensor setup characteristics, as well as the device under test, were all evaluated via finite element analysis. In light of these findings, a laboratory apparatus was constructed to investigate the impact of key measurement factors[38][39][40][41].…”
mentioning
confidence: 99%
“…Resulst showed that the die life improved by the application of gas nitriding treatment. K. Ali et al [34] have studied the attenuation of heat treated S55c carbon steel which was measured by ultrasonic test. Annealing, tempering and quenching heat treatment processes were done on S55c carbon steel and its effects in attenuation was measured on UT (ultrasonic test).…”
Section: E) Microwave Heat Treatmentmentioning
confidence: 99%
“…Over $450 million was invested in UAV start-ups just few years ago [11]. While non-contact based UAV inspection, such as visual, optical, infrared, LIDAR, and gas detectors, is quickly becoming a commodity, significant progress must still be made in aerial robotics and nondestructive testing (NDT) measurement technology to enable traditional contact NDT, such as Ultrasound testing (UT), Giant Magnetoresistance (GMR), and Eddy-Current testing (ECT) [12]- [15].…”
Section: Introductionmentioning
confidence: 99%